Adverse working conditions in Romanian out-of-hours primary care (OOH-PC): an interview study - Simona Ciotlăuș; Marius Ionuț Ungureanu; Florin Oprescu (Human Resources for Health)
Abstract Background Adverse working conditions in Romanian out-of-hours primary care (OOH-PC) are a growing concern due to the shortage of healthcare professionals, outmigration, and inadequate measures to address the retirement of family doctors. This has led to significant fluctuations in the number of OOH-PC centres across the country. To address the existing knowledge gaps regarding the OOH-PC services, this study aimed to explore the challenges faced by healthcare workers in after-hours care. Methods A qualitative approach was used to gather insights from 14 healthcare professionals, including family doctors, nurses, representatives of professional associations, emergency doctors, and paediatricians. Through thematically analyzed in-depth semi-structured interviews, the researchers examined the working conditions in OOH-PC in Romania from the perspective of healthcare workers. Results Data analysis yielded five key themes related to adverse working conditions in OOH-PC: working hours and shift length, increasing workload and patient influx, obstacles to achieving work–life balance, inconveniences related to OOH center premises (rest space, security), and insufficient financial compensation for after-hours health service provision. Conclusions In the context of systemic changes in the Romanian health system, this article provides valuable information on the current working conditions of primary care health workers in OOH care. It highlights the importance of improving working conditions to attract and retain healthcare professionals in OOH-PC.